Interpreting Scientific Explanations in Ecosystem Learning: A Transcendental Phenomenological Study of Fifth-Grade Elementary Students' Conceptual Understanding - Awanda, Ifan; Insih Wilujeng; Woro Sri Hastuti; Dewi Astuti (UIN Sunan Kalijaga Yogyakarta, 2026)
Elementary school students' conceptual understanding of ecosystems is often hindered by misconceptions and a lack of active interpretation of scientific explanations. Mastering ecosystem concepts from an early age is a crucial foundation for scientific literacy at higher education levels. This transcendental phenomenological study aims to explore the essence of fifth-grade students' experiences in interpreting scientific explanations toward conceptual understanding in ecosystem learning. A qualitative approach with Moustakas' transcendental phenomenological design was employed at a public elementary school in Kedaton District, Bandar Lampung. The research population was all fifth-grade students in the odd semester of the 2025/2026 academic year (28 students). All 28 students were involved in observations, and 12 students were purposively selected for in-depth interviews. Data were collected through semi-structured interviews, participant observations, and document analysis. The phenomenological reduction process yielded three essential themes: cognitive-emotional tension as an entry point for interpretation, contextual explanation as a bridge to understanding, and group discussion as an intersubjective space for meaning reinforcement. The essence of the experience shows that students' interpretation occurs through a circular movement from initial tension toward resolution mediated by explanations connected to students' concrete world. In other words, students do not passively receive information but actively interpret, test, and validate scientific explanations through cognitive, affective, and social experiences. This study concludes that scientific explanations are actively interpreted through interrelated cognitive, affective, and social processes. The theoretical contribution is enriching the conceptual change model with affective and intersubjective dimensions in the elementary education context.